Effect of geolocation database update algorithms to the use of TV white spaces - Ojaniemi, J.; Poikonen, J.; Wichman, R. (2012 7th International ICST Conference on Cognitive Radio Oriented Wireless Networks and Communications (CROWNCOM), 2012)
According to the European Electronic Communications Committee a practical approach for constructing a cognitive radio network operating in TV white spaces is based on geolocation databases. The practical communication rates achievable for the secondary users and the interference caused to the primary system are fundamentally limited by the information the database has on the geographical distribution of spectrum occupation, and how this information is used to assign transmission power limits to white space devices. In this work we present practical methods for improving the accuracy of the geolocation databases by simulating spectrum sensing samples obtained in a cellular-type white space system operating within the primary TV network area. Furthermore, we analyze the effect of the considered methods on the secondary system throughput and intereference levels on the primary system.